Effect of Hypothermia on Erythrocyte Sensitivity to Post-Hypertonic Shock at Neurological Disease - Morozova, Oksana M.; Batyuk, Liliya V.; Muraveinik, Oksana A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 186.